Hygiene Ibu dan Sanitasi Dapur Rumah Tangga dengan Kejadian Stunting pada Balita - Halawa, Elfredo Josua; Suaib, Fatmawaty; Fanny , Lydia (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2025)
Stunting is a condition of growth failure in children under 5 years of age caused by chronic malnutrition, repeated infections, and lack of adequate psychosocial stimulation. The prevalence of stunting in South Sulawesi in 2024 was still 23.4%. The purpose of this study was to analyze the relationship between maternal hygiene in food processing and household kitchen sanitation with the incidence of stunting in toddlers. The study design used was an analytical observational with a cross-sectional approach, involving 43 toddlers aged 6–59 months in the working area of ​​the Sudiang Raya Community Health Center, Makassar City. Maternal hygiene data were obtained through the WHO Five Keys to Safer Food questionnaire, while kitchen sanitation data were based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. The nutritional status of toddlers was measured through anthropometry and analyzed using the chi-square test. The results showed that 25 toddlers (58,1%) were stunted and 18 toddlers (41.9%) were normal. There was a significant relationship between maternal hygiene and the incidence of stunting (p = 0.018) and between household kitchen sanitation and the incidence of stunting (p = 0.004). Thus, it can be concluded that improving maternal hygiene behavior and kitchen sanitation can be an effective strategy for preventing stunting by reducing the risk of recurrent infections in toddlers.